Assessing Signal-Driven Mechanisms in Neonates: Brain Responses to Temporally and Spectrally Different Sounds - Minagawa-Kawai, Yasuyo; Cristià, Alejandrina; Vendelin, Inga; Cabrol, Dominique; Dupoux, Emmanuel (Frontiers in Psychology, 2011)
Past studies have found that in adults that acoustic properties of sound signals (such as fast vs. slow temporal features) differentially activate the left and right hemispheres, and some have hypothesized that left-lateralization for speech processing may follow from left-lateralization to rapidly changing signals. Here, we tested whether newborns’ brains show some evidence of signal-specific lateralization responses using near-infrared spectroscopy (NIRS) and auditory stimuli that elicits lateralized responses in adults, composed of segments that vary in duration and spectral diversity. We found significantly greater bilateral responses of oxygenated hemoglobin (oxy-Hb) in the temporal areas for stimuli with a minimum segment duration of 21 ms, than stimuli with a minimum segment duration of 667 ms. However, we found no evidence for hemispheric asymmetries dependent on the stimulus characteristics. We hypothesize that acoustic-based functional brain asymmetries may develop throughout early infancy, and discuss their possible relationship with brain asymmetries for language.